Application of quantitative systems pharmacology to guide the optimal dosing of COVID‐19 vaccines. (12th August 2021) - Giorgi, Mario; Desikan, Rajat; van der Graaf, Piet H.; Kierzek, Andrzej M.
Abstract : Optimal use and distribution of coronavirus disease 2019 (COVID‐19) vaccines involves adjustments of dosing. Due to the rapidly evolving pandemic, such adjustments often need to be introduced before full efficacy data are available. As demonstrated in other areas of drug development, quantitative systems pharmacology (QSP) is well placed to guide such extrapolation in a rational and timely manner. Here, we propose for the first time how QSP can be applied in the context of COVID‐19 vaccine development.